Capnography during cardiac arrest. (November 2018) - Sandroni, Claudio; De Santis, Paolo; D'Arrigo, Sonia
Abstract: Successful resuscitation from cardiac arrest depends on provision of adequate blood flow to vital organs generated by cardiopulmonary resuscitation (CPR). Measurement of end-tidal expiratory pressure of carbon dioxide (ETCO2 ) using capnography provides a noninvasive estimate of cardiac output and organ perfusion during cardiac arrest and can therefore be used to monitor the quality of CPR and predict return of spontaneous circulation (ROSC). In clinical observational studies, mean ETCO2 levels in patients with ROSC are higher than those in patients with no ROSC. In prolonged out of hospital cardiac arrest, ETCO2 levels <10 mmHg are consistently associated with a poor outcome, while levels above this threshold have been suggested as a criterion for considering patients for rescue extracorporeal resuscitation. An abrupt rise of ETCO2 during CPR suggests that ROSC has occurred. Finally, detection of CO2 in exhaled air following intubation is the most specific criterion for confirming endotracheal tube placement during CPR. The aetiology of cardiac arrest, variations in ventilation patterns during CPR, and the effects of drugs such as adrenaline or sodium bicarbonate administered as a bolus may significantly affect ETCO2 levels and its clinical significance. While identifying ETCO2 as a useful monitoring tool during resuscitation, current guidelines for advanced life support recommend against using ETCO2 values in isolation for decision making in cardiac arrestmanagement.